REF-DELIVERY project plan: electronic reference service - Ahmed Helal; Nashat Mahfouz; Haniyeh Aqeela; Amany Saudi; Saida Al-Mabrouk; Afrah Hassan (Cybrarians Journal, 2023)
The idea of ​​the project is to create a website (www.refdelivery.com) that aims to provide a reference service in six university libraries: (6 October University Library for Modern Sciences and Arts MSA - Khartoum Applied College Library - Omar Al-Mukhtar University Library in Al-Bayda City - Palestine University Library Technical attendance - Benghazi University Library - Faculty of Computers and Information Library, Fayoum University) in order to respond to reference inquiries for library users, including students, faculty members, and graduate students.